Ruptured splenic abscess presenting as peritonitis: a case report - Shetty, Mahendra Kumar; Kagali, Nagaraj A.; Latha, G. A. (International Journal of Research in Medical Sciences, 2017)
Incidence of splenic abscess is a rare -0.05-0.7% and rarer still is the rupture of the abscess. We present a patient who presented with features of peritonitis and investigations and emergency laparotomy revealed a ruptured splenic abscess with dense adhesions between spleen and diaphragm, stomach, splenic flexure, kidney and lateral abdominal wall due to perisplenitis. Patient was treated with emergency splenectomy and antibiotics. Patient recovered although after a stormy immediate post operative period due to septicaemia. This case is presented owing to the rarity of presentation.